Proyeksi Kebutuhan Air Bersih Kabupaten Karawang Tahun 2024-2044 - Hasan, Muwaffaq Saparudin; Adzillah, Wilma Nurrul; Mentari, Okti Dinasakti Nurul (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Karawang Regency, as an area experiencing rapid population growth and industrial development, faces serious challenges in the provision of clean water. This study aims to project the clean water demand in Karawang Regency up to the year 2044 using a quantitative descriptive method and an exponential projection model. The data used include population figures, clean water customer data, and the volume of water sold by Perumdam Tirta Tarum. The projection results indicate a significant increase in clean water demand from 898,17 liters/second in 2024 to 7.970,48 liters/second in 2044. This increase is driven by population growth, expanded service coverage, and the development of non-domestic sectors. The results of this study are expected to serve as a basis for sustainable clean water supply system planning in Karawang Regency.